9 Psychopathology & the nature of the Self. Issue 12 (14th November 2022) - Oyebode, Femi
Abstract : Femi Oyebode graduated from University of Ibadan with distinction in Medicine in 1977 &amp trained as a psychiatrist in Newcastle-Upon-Tyne. He has been Consultant Psychiatrist in Birmingham since 1986 &amp retired in 2021. He has been Honorary Professor of Psychiatry at the University of Birmingham since 1999. He was Head of Department of Psychiatry from 2003–2009. He is Honorary Professor, Department of Anthropology & African Studies University of Birmingham. He is Associate Editor the British Journal of Psychiatry, & on the Editorial Boards of BJPsych Bulletin and BJPsych Advances. He was Chief Examiner of the Royal College of Psychiatrists from 2002 to 2005. He has been ASB Visiting Professor at University of Auckland, Raine Visiting Professor at University of Western Australia, & Visiting Professor University of Ibadan. His research interests include clinical psychopathology, delusional misidentification syndromes, medical humanities and medical ethics. He is author of Sims' Symptoms in the Mind (4–6th editions), Psychopathology of Rare and Unusual Syndromes, Madness and the Theatre and edited Mindreadings: Literature and Psychiatry. He is also a poet and literary critic. His volumes of poetry include Naked to your softness & other dreams, Master of the Leopard Hunt and Adagio for Oblong Mirrors. He contributed critical essays to the Oxford Companion to 20th century Poetry and Oxford Companion to Modern Poetry. He received the Royal College of Psychiatrists' Lifetime Achievement Award in 2016 and the highest award of the Royal College of Psychiatrists, the Honorary FRCPsych., in 2019. Abstract: Psychopathology is the systematic study of abnormal psychological experience and includes the precise description, definition and categorisation of abnormal phenomena. In this lecture I will focus on the potential role of psychopathology as a means of revealing the underlying brain processes that make possible our experience of reality. I will examine phantom limb phenomenon, Charles Bonnet Syndrome, musical hallucinations and autoscopy to illustrate and develop my thesis. My ultimate aim is to demonstrate that the value of psychopathology is over and above the merely descriptive and that its value includes theorising about neural mechanisms.